Clickbaits, violência e arte pública na Quinta do Mocho, Loures - Chaves, Henrique (Trabalhos de Antropologia e Etnologia, 2020)
There is a pre-established image that is perpetuated about social neighbourhoods which connotes them with problems related to violence, social noxiousness and delinquency. The construction starts, usually, from outside the neighbourhoods, supported by generalised examples and then objectifying a specific image. This process propagates the already existing problem of exclusion in this neighbourhoods. The exclusion operates on different levels, as the lack of access to the most basic social rights for their inhabitants is an example. I consulted several articles from journalistic sites published online between the period of 2011-2015, were analysed. We proceeded to collect online in the respective places through searching using terms leading to relevant news articles. This article has as its objective to observe the construction of an image of the neighbourhood – the Quinta do Mocho – where simultaneously there is a project in development, dedicated to the creation of a gallery of public art, supported by the local authority. This project consists in the realisation of street art murals which cover the sides of the neighbourhood’s building, thus fabricating a positive image of the neighbourhood, countering the mediatic negativism. This work pretends to understand how Portuguese newspapers construct and change the image of this neighbourhood, through the changes operated in it.